2019
DOI: 10.1111/sed.12547
|View full text |Cite
|
Sign up to set email alerts
|

Redeposition of volcaniclastic sediments by a tsunami 4600 years ago at Kushima City, south‐eastern Kyushu, Japan

Abstract: The Hyuga‐nada Sea, south‐eastern Kyushu, Japan, is located between a strong (Nankai Trough) and a weak interplate coupling zone (Ryukyu Trench). Over the past 400 years this area has only experienced Magnitude 7·5 earthquakes or smaller and associated small‐scale tsunamis. However, this short historical record most likely does not include the full range of high magnitude, low frequency giant earthquakes that might have occurred in the region. Thus, it is still unclear whether giant earthquakes and their assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Other not‐yet described pre‐historical tsunami events were studied by Yamada et al . () on south‐eastern Kyushu (Japan). Due to its sedimentological and palaeontological character, a singular reddish‐brown pumiceous layer preserved in a fully non‐marine, organic‐rich mud sequence obtained from onshore sediment cores, is associated with a tsunami inundation.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Other not‐yet described pre‐historical tsunami events were studied by Yamada et al . () on south‐eastern Kyushu (Japan). Due to its sedimentological and palaeontological character, a singular reddish‐brown pumiceous layer preserved in a fully non‐marine, organic‐rich mud sequence obtained from onshore sediment cores, is associated with a tsunami inundation.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Further south at Kushima City (Fig. 2, site 6), Yamada et al (2020) conducted paleotsunami research and found only one tsunami deposit at 4600 years ago during the period between 2000 and 5000 years ago. Based on this result, they suggested that tsunamigenic earthquakes probably only occur at low frequencies in the Hyūga-nada region.…”
Section: Paleotsunami Depositsmentioning
confidence: 99%
“…Historical records suggest no large earthquakes with magnitude >8 have occurred over the last 400 years in this region. Geological evidence from the Pacific coast of central and southern Kyushu is probably still insufficient to discuss paleoseismicity in this region, although recent works suggest the rare occurrence of tsunamigenic earthquakes (Ichihara et al, 2015;Yamada et al, 2020).…”
Section: Hyūga-nada and The Ryukyu Subduction Zonementioning
confidence: 99%